A comparative study of transabdominal and transvaginal ultrasound guidance on consequences of embryo transfer at Mahdiyeh hospital of Tehran in 2020: An RCT - Paria Geran Malekkheili; Shahrzad Zadehmodarres; Zahra Heidar (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Infertility is an important problem that affects many couples worldwide. Assisted reproductive technology (ART) helps infertile couples to have offspring. One of the critical parts of ART is embryo transfer (ET). Objective: To compare the effect of transvaginal and transabdominal ultrasonography-guided ET on ART outcomes. Materials and Methods: In this randomized clinical trial study, 90 women who were candidates for in vitro fertilization (IVF) referred to Mahdiyeh hospital of Tehran, Iran during the yr 2020 were randomly divided into two groups (n = 45/each) of transvaginal and transabdominal ultrasonography-guided ET. The embryos were transferred two-three days after oocyte retrieval. The patient pain, duration and difficulty of the procedure, three-dimensional vision quality and successful pregnancy rate were measured. Results: In this study, 63.2% of the 45 women who underwent IVF under the guidance of the transvaginal guidance and 36.8% of the 45 women who underwent IVF under the transabdominal guidance had a successful pregnancy, which was not significantly different (p = 0.19). Also, based on other results there was no difference between the two groups in terms of patient pain (p = 0.53), duration (p ≥ 0.50), difficulty of procedures (p ≥ 0.50) and ultrasonography vision; however, the three-dimensional vision quality in the transvaginal ultrasonography was better than that in the transabdominal ultrasonography (p < 0.01). Conclusion: Overall, the ART outcomes in the transvaginal and transabdominal ultrasonography-guided ET were similar, so we suggest that physicians evaluate the patient's situation, the hospital equipment, and their ability before selecting the type of ultrasonography.